A case of cervical cystic vagal schwannoma mimicking a lateral neck cyst. Issue 4 (July 2021) - Ono, Shoya; Hasegawa, Shogo; Miyabe, Satoru; Takeuchi, Go; Morishita, Yoshihisa; Ando, Michiyo; Koie, Shin; Kondo, Yutaro; Masaki, Michihiro; Nagao, Toru
Abstract: Cervical cystic vagal schwannomas sometimes mimic lateral neck cysts because of their extremely rare cystic appearance. Accurate diagnosis of this tumor and preservation of neural function are important because permanent neural injury may occur in patients with cervical schwannomas. During surgery, tumor enucleation of the true capsule of the tumor protects the nerve of origin. In this report, we discuss the case of a 27-year-old woman with cervical cystic vagal schwannoma mimicking a lateral neck cyst, who underwent successful tumor enucleation without suffering permanent neurological deficits. This case report aimed to present the extremely rare cystic changes that may occur in cervical schwannomas, and to improve diagnostic accuracy in relation to this disease. Herein, we discuss the details of enucleation, the methodology of which has not been standardized, and advocate the need for surgery in accordance with the pathogenesis of schwannoma.